Magnetotransport studies of optimally doped Sr(Fe1−xCox)2As2. (21st November 2018) - Kumar, Rohit; Harnagea, Luminita; Lakhani, Archana; Nair, Sunil
Abstract: We report magnetotransport measurements and their scaling analysis for the optimally electron-doped Sr(Fe0.88 Co As2 system. We observe that both the Kohler's and modified Kohler's scalings are violated. Interestingly, the Hall angle displays a quadratic temperature dependence (cot T 2 ) similar to many cuprates and heavy fermion systems. The fact that this T 2 dependence is seen in spite of the violation of modified Kohler's scaling suggests that the Hall angle and magnetoresistance are not governed by the same scattering mechanism. We also observe a linear magnetoresistance in this system, which does not harbor a spin density wave ground state. Implications of our observations are discussed in the context of existing models for the magnetotransport of these strongly correlated electron systems.